2012
DOI: 10.1007/s11033-012-2355-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel nucleotide changes in mutational analysis of mitochondrial 12SrRNA gene in patients with nonsyndromic and aminoglycoside-induced hearing loss

Abstract: Mitochondria have essential role in cellular energy metabolism and defects in their function lead to many metabolic diseases. Mitochondrial DNA (mtDNA) mutations have been associated with number diseases such as nonsyndromic and aminoglycoside-induced hearing loss. Mutational screening of entire 12SrRNA and tRNA (ser (UCN)) genes in 107 unrelated Iranian patients with amino glycoside-induced and nonsyndromic bilateral hearing loss by direct sequencing analysis method were performed. Twenty different homoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“… 31 , 59 , 60 , 62 64 However, consistent with the other studies, 58 61 , 65 , 66 our study showed that even in the absence of aminoglycoside exposure, mitochondrial polymorphisms could be responsible for hearing impairment. Previous studies revealed the mitochondrial m1555A>G, 67 m.1005T>C, 68 and m.921T.C 68 mutations among Iranian patients, while these mentioned mutations were not detected in our patients with HL. Additionally, a study indicated the high carrier frequency of the nuclear GJB2 mutation (35delG) in the north of Iran.…”
Section: Discussioncontrasting
confidence: 70%
“… 31 , 59 , 60 , 62 64 However, consistent with the other studies, 58 61 , 65 , 66 our study showed that even in the absence of aminoglycoside exposure, mitochondrial polymorphisms could be responsible for hearing impairment. Previous studies revealed the mitochondrial m1555A>G, 67 m.1005T>C, 68 and m.921T.C 68 mutations among Iranian patients, while these mentioned mutations were not detected in our patients with HL. Additionally, a study indicated the high carrier frequency of the nuclear GJB2 mutation (35delG) in the north of Iran.…”
Section: Discussioncontrasting
confidence: 70%
“…However, the precise mechanism of aminoglycoside interaction with rRNA is still under investigation [ 46 ]. Other mutations of mitochondrial DNA associated with aminoglycoside hypersusceptible hearing loss have been found in a recent study [ 47 ].…”
Section: Hearing Loss Induced By Ototoxic Drugsmentioning
confidence: 97%
“…A lack of introns and protective histones make mtDNA more susceptible to ROS and other types of damage, which could lead to sequence mutations or copy number alterations. 12 Variation of both quality (mutations) 13 , 14 and quantity (copy number) 15 of mtDNA has been associated with many human diseases, including neurodegenerative diseases, 16 metabolic diseases, and various types of cancer, 17 as well as in the process of aging. 18 Therefore, the application of mtDNA alteration as a biomarker in aging, age-related diseases, cancers, metabolic diseases, and even forensic science is currently being investigated.…”
Section: Introductionmentioning
confidence: 99%